Polymers with Side Chain Porosity for Ultrapermeable and Plasticization Resistant Materials for Gas Separations. Issue 21 (9th April 2019) - He, Yuan; Benedetti, Francesco M.; Lin, Sharon; Liu, Chao; Zhao, Yanchuan; Ye, Hong‐Zhou; Van Voorhis, Troy; De Angelis, M. Grazia; Swager, Timothy M.; Smith, Zachary P.
Abstract: Polymer membranes with ultrahigh CO2 permeabilities and high selectivities are needed to address some of the critical separation challenges related to energy and the environment, especially in natural gas purification and postcombustion carbon capture. However, very few solution‐processable, linear polymers are known today that access these types of characteristics, and all of the known structures achieve their separation performance through the design of rigid backbone chemistries that concomitantly increase chain stiffness and interchain spacing, thereby resulting in ultramicroporosity in solid‐state chain‐entangled films. Herein, the separation performance of a porous polymer obtained via ring‐opening metathesis polymerization is reported, which possesses a flexible backbone with rigid, fluorinated side chains. This polymer exhibits ultrahigh CO2 permeability (>21 000 Barrer) and exceptional plasticization resistance (CO2 plasticization pressure > 51 bar). Compared to traditional polymers of intrinsic microporosity, the rate of physical aging is slower, especially for gases with small effective diameters (i.e., He, H2, and O2 ). This structural design strategy, coupled with studies on fluorination, demonstrates a generalizable approach to create new polymers with flexible backbones and pore‐forming side chains that have unexplored promise for small‐molecule separations. Abstract : A porous polymer featuring a flexible backbone and rigid, fluorinated side chains is prepared via ring‐opening metathesis polymerization. This polymer exhibits ultrahigh CO2 permeability (>21 000 Barrer) and exceptional plasticization resistance (CO2 ‐induced plasticization pressure > 51 bar). By generating ultramicroporosity through predesigned side chains instead of the polymer backbone, a promising new design strategy is presented for gas‐separation membranes.